Radiographic and radiological assessment of laminitis. (6th September 2013) - Sherlock, C.; Parks, A.
Summary: Radiographic studies are an essential component in evaluation of horses with laminitis. The standard radiographs that should be obtained to aid assessment of horses with laminitis are the lateromedial, horizontal dorsopalmar and dorsal 45° proximal palmarodistal oblique views. This article will summarise the assessment of these 3 projections in the laminitic horse as well as discuss the prognostic significance of common radiological abnormalities in horses with laminitis.